2017
DOI: 10.1364/oe.25.007465
|View full text |Cite
|
Sign up to set email alerts
|

Spatial asymmetry of optical parametric fluorescence with a divergent pump beam and potential applications

Abstract: The spatial distribution of the optical parametric fluorescence generated in a negative uniaxial nonlinear crystal is asymmetric with respect to the pump when the pump beam has a slight divergence angle. The formation mechanism of this phenomenon and the influence of parameters were analyzed and discussed from a theoretical standpoint. Moreover, two potential applications of this phenomenon were experimentally demonstrated, showing the temporal contrast improvement of ultra-intense lasers and the intensity enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The gain bandwidth broadening in the optical parametric process with a divergent or convergent pump/signal beam has been demonstrated, [138][139][140][141][142] and the mechanism is the same as the multiple-beam pumped OPCPA. In a recent study, as shown in Figure 11a, we shaped the pump from a collimated single [145] Copyright 2021, Springer Nature.…”
Section: Wide-angle Noncollinear Opcpa (Wnopcpa)mentioning
confidence: 92%
See 1 more Smart Citation
“…The gain bandwidth broadening in the optical parametric process with a divergent or convergent pump/signal beam has been demonstrated, [138][139][140][141][142] and the mechanism is the same as the multiple-beam pumped OPCPA. In a recent study, as shown in Figure 11a, we shaped the pump from a collimated single [145] Copyright 2021, Springer Nature.…”
Section: Wide-angle Noncollinear Opcpa (Wnopcpa)mentioning
confidence: 92%
“…The gain bandwidth broadening in the optical parametric process with a divergent or convergent pump/signal beam has been demonstrated, [ 138–142 ] and the mechanism is the same as the multiple‐beam pumped OPCPA. In a recent study, as shown in Figure a, we shaped the pump from a collimated single beam into multiple collimated and spatially overlapped beamlets but having individual propagating directions by a “beam homogenizer,” [ 143 ] which consisted of a lens array and a Fourier lens, resulting in several phase‐matching conditions satisfied in a single amplifier.…”
Section: Ultrabroadband Pulse Amplificationmentioning
confidence: 99%
“…The optimization of the phase-matching is given in Supplementary material. Here, we choose the phase-matching direction with a smaller signal propagation angle (compared with those of two pumps), because the angle-gap between two pump-beamlets is enlarged 54,55 . These parameters together with other parameters are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…It can be understood as the spontaneous splitting of pump photons to signal and idler photons and then being amplified along the nonlinear crystal together with seed pulses. As one main type of noise in OPCPA, PSF delivered to the target before the arrival of the main pulse may radically change the conditions of the interactions, so it has gained much attention in past decades [23][24][25][26][27][28].…”
Section: Methodsmentioning
confidence: 99%